Comparative Study of Surgical Treatment of Chalazion (Faridpur Medical College Journal, 2015)
A chalazion is chronic lipogranulomatous inflammatory lesion caused by blockage of meibomian gland orifices & stagnation of sebaceous secretion. Common practices in treatment of chalazion are intralesional steroid injection, incision & curettage and excision of chalazion. Recurrence rate is high for incision & curettage in case of large chalazion. The aim of the study is to established that excision large chalazion give better result than incision & curettage. The study was carried out at Diabetic Association Medical College & Hospital, Faridpur and General Hospital, Fadidpur. A total 100 cases were selected for study. Technique of operation were incision & curettage through conjunctival surface and excision of chalazion through skin surface. In 50 % cases we performed incision & curettage both in small (size 5mm) chalazion. In 50 % cases of large chalazion we performed excision of chalazion. The follow up period was 3 months to 6 months. In group -A with incision & curettage through conjunctival surface, in case of small chalazion 27 out of 30 patients were cured (90%). In case of large chalazion 14 out of 20 patients were cured (70%). In group B with excision of chalazion through skin surface, in case of large chalazion 49 out of 50 patients were cured (98%). So higher success rate after excision of large chalazion through skin surface.Faridpur Med. Coll. J. 2014;9(2): 68-69